Analisis Faktor-Faktor yang Melatarbelakangi Preferensi Menabung Santri di Tabungan Santri Mandiri, Pondok Pesantren Raudlatul Ulum 1, Ganjaran, Gondanglegi, Malang - Romli , Syifaur ; Fanani, Zainudin (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2019)
This study aims to conduct an analysis related to the analysis of factors that influence students' interest in saving at the Tabungan Santri Mandiri in the Islamic Boarding School of Raudlatul Ulum 1 Ganjaran Gondanglegi Malang. This research is qualitative using the documentation and an interview in method of data collection. The conclusion of this research is that the factors underlying the saving preferences of students are positive factors which are things that can be a stimulus for their interests and motivation to carry out the obligation to save. These factors include: the existence of remaining allowance, future investment, an adherence to regulations to the influence of the surrounding environment. Second, things that can be an obstacle to their interest and motivation to be reluctant to carry out the obligation to save include the lack of socialization, poor service, economic limitations and others.